Exploring Reading Comprehension Difficulties among First-Semester Students in Statistics and Computer Systems Engineering at Universitas AKPRIND Indonesia - Suprih Ambawani; Siti Saudah; Bernadetta Eko Putranti (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study explores the reading comprehension difficulty encountered by first-semester students in the Statistics Department and Computer Systems Engineering Department at Universitas AKPRIND Indonesia. A descriptive quantitative design was employed, involving 25 students. Data were obtained using a 50-item reading comprehension test and a structured questionnaire. The reading comprehension test covers six reading subskills: identification of the main idea, recognition of references, inferencing, vocabulary knowledge, locating specific information, and understanding detailed information. The findings show that students from both departments still face significant difficulty in comprehending reading texts, as reflected in their low-test performance. Understanding vocabulary was the most difficult aspect (71.08%), followed by determining the main idea (62.67%), making inferences (52.8%), finding detailed information (44%), finding specific information (35.5%), and identifying references (23.33%). The study also revealed that students’ reading comprehension difficulties were influenced by both internal and external factors. Internal factors included limited vocabulary, weak grammatical competence, low reading strategies, and poor concentration. External factors included limited family support and insufficient English learning resources. The study recommends that instructional efforts should focus on systematic vocabulary development, explicit grammar instruction, effective reading strategies, and increased access to English reading materials to improve students’ reading comprehension.